Literature Study: Evaluation of Community-Based Stunting Prevention Policies - Sri Wahyuningsih; Joyce Angela Yunica; Vivi Oktari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stunting in children under five remains a significant public health problem in Indonesia and has long-term implications for human capital development. Community based stunting prevention policies play a crucial role in addressing this issue, particularly at the local level. This study aimed to evaluate the implementation and effectiveness of community-based stunting prevention programs in the Palembang region using a literature review approach. Relevant articles were obtained from national and international databases, including Google Scholar, PubMed, Science Direct, and the Garuda Portal, limited to publications from 2019 to 2024. Selected articles were analyzed qualitatively using thematic analysis to identify key aspects of program implementation, supporting factors, and barriers. The findings indicate that community-based stunting prevention programs in Palembang have generally been implemented in accordance with national policies and have contributed positively to improving child nutritional status. Program effectiveness was strongly supported by the active involvement of health workers and community health cadres, locally adapted intervention innovations, and cross-sectoral collaboration. However, several challenges remain, including logistical constraints, inconsistent monitoring systems, limited family participation, and suboptimal communication strategies. In conclusion, strengthening community engagement, enhancing program sustainability, and improving monitoring and evaluation mechanisms are essential to optimize the impact of community-based stunting prevention programs and ensure sustainable stunting reduction at the local level.